Bottom-Up Approaches to Rural Water Security: Evidence from a Community-Based WASH Project in Nigeria - Damilola Olajubutu; Happiness Opeyemi Agboola; John Adeleye; Ayodeji Oladimeji; Feranmi Adebunmi (The Indonesian Institute of Science and Technology Research, 2026)
Access to clean water remains a critical challenge in rural Nigeria, with over 60 million people lacking safe drinking water. This study examines a bottom-up, community-based WASH intervention implemented by the Rural Nurture Initiative in rural communities in southwestern Nigeria. Employing a qualitative single case study approach, the research used in-depth interviews with local leaders and focus group discussions with project beneficiaries. Results revealed that community participation in project design, implementation, and monitoring fostered a sense of ownership and contributed to project sustainability. Community preference for well water infrastructure over solar boreholes highlighted the importance of contextually appropriate technology selection. Additionally, WASH education components significantly improved hygiene practices among beneficiaries. The study concludes that participatory approaches to rural water provision are essential for sustainable community development and recommends that policies promoting community ownership and participatory water resource management be advanced to address water challenges in rural Nigeria.